The Influence of the Implementation of Extracurricular Activities of the Islamic Propagation Agency on the Practice of Religious Worship at Mutia Rahma Bulu Cina Middle School, Hamparan Perak District - Isma, Nurul; Yusuf, Muhammad (Lembaga Riset Mutiara Akbar, 2025)
This study is motivated by the importance of extracurricular activities in supporting the development of character and worship experiences of students at SMP Mutia Rahma Bulu Cina. The full-day education system in this school requires additional activities that can help shape students' religious values. This study aims to analyze the level of implementation of the Islamic Propagation Agency's extracurricular activities and their influence on students' worship experiences. The research method used is quantitative with a survey approach to 33 students. The results of the study showed that student involvement in the Islamic Propagation Agency's activities had a significant effect on their worship experiences. The participation indicator showed that 42.4% of students agreed that these activities improved their worship, while 27.3% strongly agreed. Activities such as congregational prayer, reciting the Koran, and Islamic studies contributed to improving understanding and practice of daily worship. Overall, this study concludes that the Islamic Propagation Agency's extracurricular activities have a positive impact on students' worship experiences, strengthening religious character, and instilling Islamic values ??that can be applied in their social lives.